10x-2=10x+6

Simple and best practice solution for 10x-2=10x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10x-2=10x+6 equation:



10x-2=10x+6
We move all terms to the left:
10x-2-(10x+6)=0
We get rid of parentheses
10x-10x-6-2=0
We add all the numbers together, and all the variables
-8!=0
There is no solution for this equation

See similar equations:

| 4x-3(x+2)+48=0 | | X^2+10^-8x–10^-14=0 | | x⁴+1/x⁴=47 | | a³+1/a³=18 | | X²-7x-260=0 | | -4÷x=-28 | | -4x=-2(-2x-4) | | 5/8x-3=-7+3/8x | | -4(x-5)=6(x+5) | | -0.5+2x=-8.5 | | 29=r+14 | | 1.8x−22=1.3x+9 | | 2.5x+6-7.5x=1 | | 9/7-m/9=4/63 | | x-6=7+6 | | 6q=7=3q-8 | | x*1.1=11000 | | xx1.1=11000 | | x^2-3900+100x=0 | | 5.3=r+6.5 | | 1/2x=1/4x-1/6 | | (x-1)(x-2)=101/(100)^2 | | .4t^2-t-4=0 | | 15x2-18x-68=0 | | 3x^2+5x-1300=0 | | 6x²+12x-18=0 | | (x−1)(x+6)=18 | | x=7,x^2-6x+4= | | 9=27^3x-5 | | 9=273^x-5 | | 42x-61=30x+23 | | 0.4y+1=1.6y-5 |

Equations solver categories